STUDENTS"™ ENTHUSIASM IN TOURISM LEARNING IN THE 7TH SEMESTER OF ENGLISH EDUCATION - Fakhira, Rasya; Fatmawati, Rini (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
Previous studies have mostly highlighted the tourism industry in general, but not many have examined tourism learning in the context of English education, especially related to student enthusiasm in following it. This study investigates the factors influencing students"™ enthusiasm for tourism learning among seventh-semester English education students at a private university in Surakarta. The research aims to understand how tourism-related materials enhance students"™ enthusiasm and engagement in the context of English Specific Purposes. Employing a qualitative descriptive approach, data were collected through classroom observations and semi-structured interviews with six purposively selected students. Observations focus on student behavior, such as active participation and attentiveness, while interviews explored personal experiences and challenges. The findings revealed that students were more enthusiastic when they perceived the material as practical and connected to real-world applications, such as career opportunities in tourism. However, increased academic pressure and workload were identified as factors that diminished enthusiasm. The study concludes that combining theoretical knowledge with hands-on learning activities can sustain student motivation and improve engagement. The implications suggest that educators should incorporate practical elements, such as interships and project-based tasks, into the curriculum to foster enthusiasm and prepare students for professional environments.